KOMUNIKASI INTERPERSONAL GURU PADA ORANG TUA DAN SISWA DALAM MENINGKATKAN MOTIVASI BELAJAR DI SEKOLAH DASAR NEGERI 34 SINGGALANG PROVINSI SUMATERA BARAT - Ahmad Suwandi; Tantri Puspita Yazid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
State Elementary School 34 Singgalang is located at the foot of Mount Singgalang, which coincides in Jorong Luhung, Jl. Lubuk Mata Kucing, Singgalang, Kec. Ten Koto, Tanah Datar Regency, West Sumatra Province. In this study the teacher used interpersonal communication to further increase the learning motivation of the students. The purpose of this study was to determine the openness, empathy, support, positive feeling, and equality of teachers to students and parents during the learning process at SDN 34 Singgalang. This study uses a qualitative research method with the concept of interpersonal communication from Joseph A Devito. Based on the results of this study found interpersonal communication and implementation of the concept of Joseph A Devito in activities carried out by teachers, students and parents of students. Keyword : Interpersonal Communication, Learn Motivation